Real-World Analysis of Weight Gain and Body Mass Index Increase Among Patients with HIV-1 Using Antiretroviral Regimen Containing Tenofovir Alafenamide, Tenofovir Disoproxil Fumarate, or Neither in the United States - Bruno Emond; Carmine Rossi; Rachel Rogers; Patrick Lefebvre; Marie-Hélène Lafeuille; Prina Donga (Journal of Health Economics and Outcomes Research)
**Background:** While some studies among patients with HIV-1 suggest that antiretroviral therapy (ART) regimens containing tenofovir alafenamide (TAF) may be associated with greater weight gain than those not containing TAF, no studies have assessed the relationship between TAF doses and weight change. **Objectives:** To evaluate weight-related outcomes among patients with HIV-1 in the United States initiating ART containing different nucleoside reverse transcriptase inhibitors and doses. **Methods:** A retrospective longitudinal study was conducted using Decision Resources Group’s electronic medical records (July 17, 2017-March 1, 2020). Adult patients with HIV-1 initiating ART (index date) containing TAF 25 mg, TAF 10 mg, tenofovir disoproxil fumarate (TDF), or neither TAF nor TDF on or after July 17, 2018, were included. Changes in weight and body mass index (BMI) from pre-index to 3, 6, 9, and 12 months post-index were compared between cohorts using mean differences obtained from ordinary least squares models adjusted for baseline characteristics. Time-to-weight and BMI increase ≥5% were compared using Cox models adjusted for baseline characteristics. **Results:** Among 1652 eligible patients (TAF 25 mg, n=710; TAF 10 mg, n=303; TDF, n=219; non-TAF/TDF, n=420), the majority (83.2%-99.5%) initiated an integrase strand transfer inhibitor, except for the TDF cohort (45.2%). Patients initiating TAF 25 mg had greater weight or BMI increase across all time points compared with patients initiating TAF 10 mg, TDF, or non-TAF/TDF regimens (mean differences in weight or BMI changes between cohorts at 12 months post-index ranged from 0.78 kg [1.72 lb] to 1.34 kg [2.95 lb] and from 0.77 kg/m2 to 1.95 kg/m2, respectively), although findings were not statistically significant for all comparisons. Compared with TAF 25 mg, time-to-weight and BMI increase ≥5% in the other treatment cohorts were longer (hazard ratios ranged from 0.77 to 0.94), although findings were generally not statistically significant. **Conclusions:** Among a population of patients predominantly initiating integrase strand transfer inhibitors, increases in weight and BMI post-ART initiation were common and appeared to be higher and occur more rapidly among patients receiving TAF 25 mg compared with lower TAF doses or other nucleosides. When considering long-term health consequences, weight gain is an important factor to consider when selecting an ART regimen.